SHORT COURSE DAN PENDAMPINGAN PAJAK PENGHASILAN, PAJAK PERTAMBAHAN NILAI AMAL USAHA MUHAMMADIYAH BIDANG PENDIDIKAN DI GRESIK, TUBAN DAN BOJONEGORO - Umaimah, Umaimah; Afiqoh, Nyimas Wardatul; Mujaddid, Abdullah (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
This activity aims to provide knowledge and skills about Income Tax and Value Added Tax for Muhammadiyah Charity Businesses in the education sector. The method of implementing activities is training and mentoring. This activity was attended by 103 Muhammadiyah school treasurers in Gresik Regency, Tuban Regency and Bojonegoro Regency. The results obtained are that after the training, the school treasurer has a good understanding of taxes, is able to calculate and report the school's tax obligations according to the provisions. Post-test results: 90% of the training participants were able to answer the questions well. Mentoring is provided to schools to ensure that schools have reported their tax obligations in accordance with applicable regulations